2020
DOI: 10.1093/jas/skaa230
|View full text |Cite
|
Sign up to set email alerts
|

The impact of feed efficiency selection on the ruminal, cecal, and fecal microbiomes of Angus steers from a commercial feedlot

Abstract: Feed is the greatest cost of animal production so reducing it is critical to increase producer profits. In ruminants, the microbial population within the gastrointestinal tract (GIT) is critical to nutrient digestion and absorption in both the rumen and the hindgut. The objective of this study was to determine the bacterial taxonomic profile of the rumen, cecum, and feces of feedlot steers at slaughter in order to link feed efficiency and the GIT bacterial populations from these 3 locations. Twenty commercial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 33 publications
9
19
2
Order By: Relevance
“…Other researchers have also shown that microbial diversity measures differed between the rumen and the feces of cattle ( 10 , 18 , 26 ). The present study found bacterial evenness and diversity to be greater in the feces of the most efficient steers which somewhat contradicts the hypothesis proposed by Shabat et al ( 9 ); however, our findings conform the biological theory regarding the intestinal environment outlined by Welch et al ( 11 ). Nutrient availability differs widely throughout the GIT of cattle, and the digesta that reaches the large intestine contains less-digestible nutrients, which are essentially non-digested nutrients that escaped ruminal microbial degradation and small intestinal digestion.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Other researchers have also shown that microbial diversity measures differed between the rumen and the feces of cattle ( 10 , 18 , 26 ). The present study found bacterial evenness and diversity to be greater in the feces of the most efficient steers which somewhat contradicts the hypothesis proposed by Shabat et al ( 9 ); however, our findings conform the biological theory regarding the intestinal environment outlined by Welch et al ( 11 ). Nutrient availability differs widely throughout the GIT of cattle, and the digesta that reaches the large intestine contains less-digestible nutrients, which are essentially non-digested nutrients that escaped ruminal microbial degradation and small intestinal digestion.…”
Section: Discussioncontrasting
confidence: 99%
“…Shabat et al ( 9 ) hypothesized that ruminal microbial populations with less richness and diversity carried out fewer, but more relevant metabolic pathways, leading to a more limited metabolite pool but with greater biological relevance in the rumen. However, in the intestinal environment, Welch et al ( 11 ) found that bacterial richness and diversity were greater in both the cecal contents and feces of steers with higher feed efficiency. Other researchers have also shown that microbial diversity measures differed between the rumen and the feces of cattle ( 10 , 18 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the present study offers new insights into the response of static and dynamic dairy cow microbiomes to different challenges. It was observed that animals with a dynamic microbiome had low fecal alpha-diversities and positive REI values, consistent with the results of previous studies on steers, where high fecal alpha-diversities correlated with low residual feed intake (RFI) ( 24 ). Animals with a dynamic microbiome, mostly associated with the C-Bifi group, were observed to have higher milk quality (milk LogSCC, protein, and fat), lower body weight, fewer health issues, and lower ketosis risk (low NEFA, BHB, and TG; high glucose and carnitine).…”
Section: Discussionsupporting
confidence: 90%